Provision of ancillary services by renewable hybrid generation in low frequency AC systems to the grid. (February 2019) - Dong, J.; Attya, A.B.; Anaya-Lara, O.
Highlights: Proposing 100% renewable Low Frequency AC system of hydro and wind power plants. The re-designed hydro generator provides ancillary services on behalf of the wind farm. The proposed smoothing method adapts both surplus and insufficient wind power generation. The proposed frequency support methods tackle successive frequency drops at the Grid. And they are tunable to be Grid Code compliant and avoid major frequency violations. Abstract: Wind energy high penetration levels in power systems lead to continuous power imbalance due to the intermittent nature of wind power. This paper proposes and investigates different methods to enable a hybrid generation system to provide frequency support to the grid. The hybrid generation is 100% renewable and composed of a wind farm and hydropower plant (HPP) of comparable generation capacities, and they are interconnected through a Low Frequency AC system (LFAC). The grid–tie is composed of a Voltage-Source Converter based High-Voltage, Direct Current (VSC-HVDC) junction that acts as frequency changer to maintain the grid nominal frequency. The HPP provides two types of ancillary services: wind power smoothing and frequency drops mitigation to avoid the use of thermal generation and battery energy storage. The paper offers different control methods to provide the two AS with improved coordination between the different controls in the hybrid generation system and complying with the common requirements of Grid Codes. The results obtained show that the frequency at the LFAC can tolerate mild drops to provide frequency support to the grid. The controllers' parameters have a clear impact on the frequency response at both systems. Simulation environment is MATLAB and Simulink.